1995
DOI: 10.1175/1520-0469(1995)052<3013:wawaom>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Windowed and Wavelet Analysis of Marine Stratocumulus Cloud Inhomogeneity

Abstract: To improve radiative transfer calculations for inhomogeneous clouds, a consistent means of modeling inhomogeneity is needed. One current method of modeling cloud inhomogeneity is through the use of fractal paramdemonstrate both the strengths and weaknesses of these models•

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Single‐point histograms of satellite, radar, and lidar measurements of optical depth or liquid water/ice path can, in principal, be used to constrain the e PDF at the 10 to 200 km spatial scales typical of mesoscale and climate model grids [ Smith and Del Genio , 2002; Carlin et al , 2002; Jeffery and Austin , 2003]. However, across this range of scales, the two‐point statistics (in particular, the scalar spectra and the structure functions) of cloud radiance or optical depth measurements typically satisfy a power law relation with a scale‐invariant exponent which indicates the presence of long‐range correlations [e.g., Cahalan and Snider , 1989; Lovejoy et al , 1993; Barker and Davies , 1992; Gollmer et al , 1995; Davis et al , 1999]. Such a power law relation implies a statistical symmetry that is usually referred to simply as “scaling.” Determining the nature and extent of this scaling is important both because the prognostic equations for the PDF moments require estimates of the unresolved statistics and because establishing the extent of long‐range correlations is a prerequisite to obtaining reliable estimates of the one‐point statistics.…”
Section: Introductionmentioning
confidence: 99%
“…Single‐point histograms of satellite, radar, and lidar measurements of optical depth or liquid water/ice path can, in principal, be used to constrain the e PDF at the 10 to 200 km spatial scales typical of mesoscale and climate model grids [ Smith and Del Genio , 2002; Carlin et al , 2002; Jeffery and Austin , 2003]. However, across this range of scales, the two‐point statistics (in particular, the scalar spectra and the structure functions) of cloud radiance or optical depth measurements typically satisfy a power law relation with a scale‐invariant exponent which indicates the presence of long‐range correlations [e.g., Cahalan and Snider , 1989; Lovejoy et al , 1993; Barker and Davies , 1992; Gollmer et al , 1995; Davis et al , 1999]. Such a power law relation implies a statistical symmetry that is usually referred to simply as “scaling.” Determining the nature and extent of this scaling is important both because the prognostic equations for the PDF moments require estimates of the unresolved statistics and because establishing the extent of long‐range correlations is a prerequisite to obtaining reliable estimates of the one‐point statistics.…”
Section: Introductionmentioning
confidence: 99%
“…This gives rise to the paradigm that WT is merely a sophisticated procedure used by mathematics specialists for pure academic pursuit and therefore has limited practical application in climate research. Recently, wavelet analyses are beginning to make inroads into the traditional atmospheric and oceanographic literature (e.g., Gambis 1992;Kumar and Foufoula-Georgiou 1993;Gamage and Blumen 1993;Gao and Li 1993;Collineau and Brunet 1993;Meyers et al 1993;Weng and Lau 1994;Gollmer et al 1995). However, given the appeal of WT for the study of nonstationary geophysical processes, there is little doubt that WT is underused and underexplored for climate research.…”
Section: Introductionmentioning
confidence: 99%
“…These measurements have shown that for wavelengths above about 2-5 m, the spectrum follows the Kolmogorov law, but below this, there is a significant departure, with the spectral index becoming about unity. Microwave radiometry has been used to measure the columnaveraged liquid-water content as a time series (converting it to a space series with the wind velocity) [20]. They find that the spectral index is −1.75, which is not far from the Kolmogorov law.…”
Section: Measurements Of Atmospheric Turbulencementioning
confidence: 99%